A 90 kb DNA deletion associated with neurofibromatosis type 1. Issue 12 (December 1990) - Upadhyaya, M; Cheryson, A; Broadhead, W; Fryer, A; Shaw, D J; Huson, S; Wallace, M R; Andersen, L B; Marchuk, D A; Viskochil, D
Abstract : A deletion of 90 kb of DNA has been identified in a patient with neurofibromatosis type 1, using pulsed field gel electrophoresis. The deletion lies between probes 17L1A and AC5 in the critical region of chromosome 17 and represents the only molecular alteration found by PFGE in a series of 90 unrelated patients. The subject showing the deletion is an isolated case, shows typical clinical features, and represents one of the first examples of a molecular deletion to be found in this disorder.